Understanding doctors’ emergency department antibiotic prescribing decisions in children with respiratory symptoms in the UK: a qualitative study - Thomas Hampton; Helen Mary Higgins; Jane Ogden (BMJ Open)
Objective Exploration of the factors that influence hospital doctors’ antibiotic prescribing decisions when treating children with respiratory symptoms in UK emergency departments.Methods A qualitative study using semistructured interviews based on a critical incident technique with 21 physicians of different grades and specialties that treat children in the UK. Interviews were audio-recorded then transcribed verbatim and analysed using thematic analysis.Results Four themes were identified. These themes illustrate factors which influence clinician prescribing. The three principal themes were authorities, pressures and risk. The fourth transcending theme that ran through all themes was clinician awareness and complicity (‘knowing but still doing’).Conclusions Hospital doctors prescribe antibiotics even when they know they should not. This appears to be due to the influence of those in charge or external pressures experienced while weighing up the immediate and longer term risks but clinicians do this with full insight into their actions. These findings have implications for invested parties seeking to develop future antimicrobial stewardship programmes. It is recommended that stewardship interventions acknowledge and target these themes which may in turn facilitate behaviour change and antimicrobial prescribing practice in emergency departments.